Yield and Nutritive Value of Cool-Season Annual Forages and Mixtures Seeded into Pearl Millet Stubble - Villalobos Villalobos, Luis Alonso (2017)
Cool-season annual forages can provide grazing for beef cattle during fall and early winter. Th e objective of this study was to evaluate yield and nutritive value of nine forage combinations seeded in early August into pearl millet (Pennisetum glaucum L.) hay stubble that was either sprayed or allowed to regrow. Grass species included spring triticale (×Triticosecale Wittmack), winter wheat (Triticum aestivum L.), and winter barley (Hordeum vulgare L.). Each grass was then combined with a brassica mixture {turnip [Brassicas rapa L. var. rapa], rape [Brassica napus L. var. napus], radish [Raphanus sativus var. oleifer Strokes], and hybrid Chinese cabbage [Brassica rapa L. chinensis) × Turnip]}. A legume mixture (hairy vetch [Vicia villosa Roth] and Austrian winter pea [Pisum sativum subsp. arvense L.]) was then added to the grass–brassica mixtures. All species and mixtures produced suffi cient forage (3080–5580 kg dry matter [DM] ha–1) to be stockpiled for fall grazing. Th e millet and brassicas dominated yield and nutritive value of the unsprayed and sprayed mixtures, respectively. Th e concentration of neutral detergent fi ber (aNDF) was greater in unsprayed than sprayed mixtures (510–579 and 229–246 g kg–1, respectively), but the concentrations of crude protein (CP) (169–180 and 185–202 g kg–1, respectively) and in vitro true digestibility (IVTD) (755–799 and 909–922 g kg–1, respectively) were less. Th e lesser nutritive value and yield potential associated with letting the millet regrow must be weighed against the extra inputs but greater yield potential and nutritive value when the regrowth is controlled prior to seeding.